Affect of Financial Development on Poverty in Iraq for the Period 1980-2010 - العبدلي, سعد عبد نجم; علي, ازهار حسن (Journal of Economics and Administrative Sciences, 2014)
There are many applied Economic studies that have found positive nexus between financial development and poverty reduction in developing countries. Iraq has witnessed an increasing rate of poverty during the period 1980-2010 due to many internal and external factors such as wars, economic sanctions, inflation, a high rate of unemployment, and political and security instability. Therefore, the investigation about the solutions to reduce poverty becomes very necessary, and enhancing the financial development in Iraq is one of these options. This is due to that the financial development could reduce the poverty rates through two channels: the first is direct via the offering of the loans and other financial facilities to the poor, and the second is indirectly through the intermediate mean which is economic growth. Whereas financial development contributes to spurring economic growth through the mobilization of savings and channel them to the most efficient uses with higher economic and social returns. In addition, economic growth reduces the poverty through two channels. The first is direct by increasing the introduction factors held by the poor and improve the situations into the sectors and areas where the poor life. The second is indirect through redistribution of the realized incomes from the economic growth as well as the realized incomes from the government revenues which can be used to transfer the payments and improve the living standard.   However, the study found that neither the financial development nor the economic growth contributed in the poverty reduction in Iraq during the period 1980-2010, and there were other factors could reduce the poverty in Iraq such as the low rate of inflation, low rate of unemployment, and the political and security stability.